Efektifitas Penggunaan EZPROXY Dalam Mengakses Jurnal Elektronik Bagi Mahasiswa Ilmu Perpustakaan Universitas Diponegoro - Stefi Melinda Saputri; Athanasia Octaviani Puspita Dewi (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2022)
This research was aimed to measure the effectiveness of using EZproxy on Single Sign On (SSO) in accessing electronic journals for Library Science students, Diponegoro University, Semarang. The analysis used a descriptive analysis method, which is a method that describes the data to get general conclusions. The sample was conducted by purposive sampling method. Collecting data was conducted by a questionnaire distributed to students as much 80 questionnaires. The results of this study are based on indicators of perceived ease of use resulting in a mean of 82.64% which is categorized as very effective; the perceived usefulness indicator produces the highest mean with a value of 83.80% which is categorized as very effective; behavioral intention to use indicator produces a mean of 79.89% which is categorized as effective; the actual system use indicator produces the lowest mean with a value of 74.7% which is categorized as effective. The results of the calculation of the mean value on all 35 statement items obtained a value of 81.25% which can be interpreted as very effective. So it can be concluded that EZproxy on Undip's E-Journal Single Sign On (SSO) service in accessing electronic journals has reached an effective level.